2016
DOI: 10.3171/2015.6.spine159
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of quality of life and functional outcome measures for cervical spondylotic myelopathy

Abstract: OBJECT Studies comparing surgical treatments for cervical spondylotic myelopathy (CSM) are heterogeneous, using a variety of different quality of life (QOL) outcomes and myelopathy-specific measures. This study sought to evaluate the relationship of these measures to each other, and to better understand their use in evaluating patients with CSM. METHODS A retrospective study was performed in all patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“… 5 Solely assessing the myelopathy is likely insufficient to fully understand clinical outcome in its totality, and combinations of questionnaires are recommended. 38 , 44 , 45 A study comparing 7 different scales, including mJOA and EMS, found that all of them detected significant improvement following surgery. 46 Still, each scale had differing qualities of reliability, validity, and responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Solely assessing the myelopathy is likely insufficient to fully understand clinical outcome in its totality, and combinations of questionnaires are recommended. 38 , 44 , 45 A study comparing 7 different scales, including mJOA and EMS, found that all of them detected significant improvement following surgery. 46 Still, each scale had differing qualities of reliability, validity, and responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“… 1 CCM is characterized by spinal cord compression due to physiologic narrowing of the sagittal diameter of the spinal canal secondary to degenerative changes in the cervical spine. 2 Its clinical presentation includes numbness, weakness, neck pain, loss of dexterity, and problems with gait. 1 , 2 Recently, intraoperative monitoring (IOM) has been increasingly used to prevent neurological impairment during spinal cord surgery.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Its clinical presentation includes numbness, weakness, neck pain, loss of dexterity, and problems with gait. 1 , 2 Recently, intraoperative monitoring (IOM) has been increasingly used to prevent neurological impairment during spinal cord surgery. 3 , 4 Changes during IOM are also associated with corresponding spinal cord functions during surgery.…”
Section: Introductionmentioning
confidence: 99%
“…While widely reported in the literature, the mJOA is an investigator-administered tool, not a patientreported outcome, and may have poor discrimination in predicting clinical outcome from the perspective of the patient. 15,30 Prior work from our group suggests that the SF-12 Physical Component Summary (PCS) is more discriminatory than the mJOA and may be less affected by length of follow-up than other scores (B Yim, A Ata, JW German: Defining substantial clinical benefit in patients undergoing surgery for cervical spondylotic myelopathy. Presentation to the 2014 AANS Annual Meeting, San Francisco, California, April 5, 2014).…”
mentioning
confidence: 99%
“…While in the past the documentation of improved clinical outcomes using patient-reported outcome has proved challenging, 14 more recent studies have reported improvements after spine surgery with patient-reported outcome measures. 2,3,6,8,11,15,[19][20][21]25,30 Some may argue that clinical outcome following surgery for DCM is best assessed by a disease-specific measure of neurological disability such as the modified Japanese Orthopaedic Association (mJOA) scale score. While widely reported in the literature, the mJOA is an investigator-administered tool, not a patientreported outcome, and may have poor discrimination in predicting clinical outcome from the perspective of the patient.…”
mentioning
confidence: 99%